Genomic Resources Notes accepted 1 February 2014 – 31 March 2014. (14th May 2014) - Genomic Resources Development Consortium; Chen, Hongjian; Lin, Gonghua; Ma, Junying; Su, Jianping; Wang, Zuyun; Whiting, Michael F.; Zhang, Tongzuo; Zhao, Fang
Abstract This article documents the public availability of transcriptome sequence data and assembled, annotated unigenes for the marmot flea, Oropsylla silantiewi.1